Glial fibrillary acidic protein and S100b protein immunoreactivity in the hippocampus of weaning rats from dams treated with acrylamide during pregnancy - Karol Rycerz; Aleksandra E. Krawczyk; Jadwiga Jaworska-Adamu; Ewa Tomaszewska; Siemowit Muszyński; Piotr Dobrowolski; Marcin Arciszewski (Folia Neuropathologica)
Acrylamide is formed at high temperature during preparation of food rich in carbohydrates. It can be found in animal feed based on potatoes and granulated wheat subjected to thermal treatment. It was demonstrated that acrylamide has a neurotoxic effect in newborn animals in both the central and peripheral nervous system after prenatal exposure to this substance. The aim of the study was to investigate the effect of acrylamide on the immunoreactivity of glial fibrillary acidic protein (GFAP) and S100b in hippocampal astrocytes of weaning rats after oral administration of acrylamide to pregnant mothers at various stages of pregnancy. The dams received acrylamide in drinking water (3 mg/kg b.w.) each day starting on the 6 th day (group II), 11 th day (group III) and 16 th day (group IV) of pregnancy. At 21 postnatal day the pups were euthanized and their brains were dissected. The immunohistochemical reactions for GFAP and S100b protein were performed on the frontal slides containing hippocampus. The obtained results demonstrated a lower density of GFAP-positive cells in rats whose mothers received acrylamide, especially for the longest time. The astrocytes from groups II and III of rats were characterized by a smaller number of processes, which were also shorter in group II. In contrast, the density of S100b-positive cells was significantly higher, especially in the group II animals. Slight alterations may be related to the low dose of acrylamide, short duration of acrylamide administration in groups III and IV, and the possibility of astrocyte regeneration during the period from delivery to weaning, when the studied substance was not administered. The findings suggest potential disruptions in the structural integrity and functional capacity of astrocytes, which are crucial in maintaining the neuronal environment and supporting hippocampal functions.